45.1k views
0 votes
Which expression is equivalent to (-5/6) / (10/3)?

1 Answer

7 votes

Answer:


(\left(-(5)/(6)\right))/(\left((10)/(3)\right))=-(1)/(4)

Explanation:

Given the expression


(\left(-(5)/(6)\right))/(\left((10)/(3)\right))

Let us solve the expression


(\left(-(5)/(6)\right))/(\left((10)/(3)\right))=(-(5)/(6))/((10)/(3))

Apply fraction rule:
(-a)/(b)=-(a)/(b)


=-((5)/(6))/((10)/(3))

Divide fractions:
((a)/(b))/((c)/(d))=(a\cdot \:d)/(b\cdot \:c)


=-(5\cdot \:3)/(6\cdot \:10)

Multiply the numbers:
6\cdot \:10=60


=-(5\cdot \:3)/(60)

Multiply the numbers:
5\cdot \:3=15


=-(15)/(60)

Cancel the common factor: 15


=-(1)/(4)

Therefore, we conclude that the equivalent expression is:


(\left(-(5)/(6)\right))/(\left((10)/(3)\right))=-(1)/(4)

User Pushpavanthar
by
5.5k points